POSSIBILITY OF USING OF SALIX BABYLONICA IN PHARMACY - E. V. Kompantseva; O. O. Frolova; T. M. Dementieva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Under review is Salix babylonica L., which is widely cultivated in Russia as an ornamental plant. The purpose of the review is to summarize the literature on the chemical composition and pharmacological activity of the Babylonian willow. In Russia, only the qualitative composition of the studied species studied, pharmacologi-cal studies have not been conducted. Abroad, there is a positive experience of Salix babylonica in folk medicine, and obtained results that indicate a high content of biologically active compounds. Shown in the survey data suggest the prospect of studying the Babylonian willows growing in the southern regions of Russia for use in medicine and pharmacy.